Faktor-faktor yang Berhubungan dengan Kadar Gula Darah pada Penderita Diabetes Melitus di Puskesmas USA, Kabupaten Bone - Kistan, Kistan; Basri, Muhammad; Sibulo, Megawati (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2024)
Diabetes Mellitus is characterized by high blood sugar levels. Puskesmas USA is one of the health centers located in Bone Regency, where in 2021, around 71 patients sought treatment with high blood sugar levels and were diagnosed with Diabetes Mellitus. The aim of this study is to determine the relationship between gender, occupation, stress level, and sleep duration with blood sugar levels in Diabetes Mellitus patients at Puskesmas USA, Bone Regency. This research uses an analytic survey method with a cross-sectional study design. The sample size for this study was 53 samples. The results of the analysis using the chi-square test in SPSS 21 showed that there is a significant relationship between gender (p value = 0.04), stress level (p value = 0.002), and sleep duration (p value = 0.004) with blood sugar levels in Diabetes Mellitus patients. However, no relationship was found between occupation (p value = 0.744) and blood sugar levels in Diabetes Mellitus patients. In conclusion, being female, having high stress levels, and inadequate sleep duration all contribute to increased blood sugar levels, thereby increasing the risk of Diabetes Mellitus. These findings emphasize the importance of lifestyle management and regular check-ups to prevent further complications. It is recommended to implement a screening program for the local community with a high risk of Diabetes Mellitus for early detection and prevention, including education on the risks of diabetes and the importance of regular health check-ups.